Low-density polyethylene films incorporated with silver nanoparticles to promote antimicrobial efficiency in food packaging - Brito, Sabrina da Costa [UNESP]; Bresolin, Joana D; Sivieri, Kátia [UNESP]; Ferreira, Marcos D [UNESP] (SAGE Publications, 2020)
Technological innovations in packaging are intended to prevent microbiological contaminations for ensuring food safety and preservation. In this context, researchers have investigated the antimicrobial effect of low-density polyethylene films incorporated with the following concentrations of silver nanoparticles: 1.50, 3.75, 7.50, 15.00, 30.00, 60.00, and 75.00 µg/ml. The films were characterized using field emission gun scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction, thermogravimetry, and differential scanning calorimetry. From the results of these techniques, it could be concluded that the silver nanoparticles incorporated in the low-density polyethylene films did not influence their physical, chemical, and thermal properties. The direct contact assays, shake-flask assays, and bacterial images obtained using scanning electron microscopy were used to analyze the antimicrobial activity of the films. In the microbial analyses, it was verified that the nanostructured films exhibited antimicrobial properties against all the microorganisms studied, although more notably for fungi and Gram-negative bacteria than the Gram-positive bacteria. Moreover, it was discovered that the packages, in which silver nanoparticles were incorporated, inhibited the growth and reproduction of bacterial cells during the early stages. These results suggest that the extruded low-density polyethylene films incorporated with silver nanoparticles may be an essential tool for improving food quality and safety.
Keywords: antimicrobial; food packaging; Polyethylene; silver nanoparticles